(untitled) (Journal of Management and Educational Sciences, 2025)
This research aims to systematically examine academic studies conducted between 2015 and 2025 on the use of Turkish music elements in piano education in Turkey. Within the scope of the study, theses and articles on the use of makam, usûl, irregular rhythm, modal melody, folk songs, and regional motifs for educational purposes in piano education were evaluated. The research was conducted using descriptive content analysis and systematic literature review methods; the data obtained were analysed using a qualitative meta-synthesis approach. The studies examined were coded in terms of the type of Turkish music element, form of use, level of education, methodological characteristics, and pedagogical contributions; they were then classified and evaluated under a thematic structure. The findings indicate that Turkish music elements are becoming increasingly visible in piano education, with a particular focus on studies related to folk song adaptations, irregular rhythm exercises, and the transfer of modal structures to the piano. Most studies have found that Turkish music materials increase student motivation, contribute to rhythmic and technical development, and foster cultural awareness. However, the limited sample size of the studies, the low methodological diversity, and the scarcity of experimental studies focused on application have been identified as significant shortcomings. In conclusion, the integration of Turkish music elements into piano education has been seen to make meaningful contributions to both the technical and cultural development of students. However, to develop the field more comprehensively, it is recommended that experimental studies on applicability at different levels of education be increased, large-sample studies be conducted, and pedagogical models be developed for transferring modal structures to the piano.